2020
DOI: 10.1002/micr.30599
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of preoperative color‐coded Duplex ultrasonography versus handheld audible Dopplers in ALT flap planning

Abstract: IntroductionThe anterior lateral thigh (ALT) flap's vascular variability can lead to complications. Thus, the accuracy of numerous planning modalities has been studied. The clinical relevance of competing mapping methods, however, remains unknown. Therefore, we compared the impact of color‐coded Duplex ultrasonography and handheld audible Dopplers on surgical efficacy and flap safety.Patients and methodsForty‐four ALT flaps were included in this comparative retrospective monocentric study. Twelve patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…(Cheng, Lin, & Chang, 2012a, 2012b. Thomas et al (2020) confirmed the superiority of CCDS to conventional Doppler US for perforator mapping and characterization prior to ALT flap harvest. Kehrer et al showed that sensitivity of PD for microvessel detection was 96.7% with a mean distance from the emergence point (true anatomy) to the projected preoperative skin marking after PD mapping (assumed anatomy) of 2.45 ± 1.90 mm (0-6 mm) (Kehrer, Hsu, Chen, Sachanandani, & Tsao, 2018).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…(Cheng, Lin, & Chang, 2012a, 2012b. Thomas et al (2020) confirmed the superiority of CCDS to conventional Doppler US for perforator mapping and characterization prior to ALT flap harvest. Kehrer et al showed that sensitivity of PD for microvessel detection was 96.7% with a mean distance from the emergence point (true anatomy) to the projected preoperative skin marking after PD mapping (assumed anatomy) of 2.45 ± 1.90 mm (0-6 mm) (Kehrer, Hsu, Chen, Sachanandani, & Tsao, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…A systematic review by Cheng et al comparing hand‐held Doppler, CCDS, and CT angiography revealed that CCDS had the highest pooled sensitivity of 95.7% as well as the highest pooled positive predictive value of 94.3% to identify microvessels for perforator flaps such as the ALT flap (Cheng, Lin, & Chang, 2012a, 2012b, 2013). Thomas et al (2020) confirmed the superiority of CCDS to conventional Doppler US for perforator mapping and characterization prior to ALT flap harvest. Kehrer et al showed that sensitivity of PD for microvessel detection was 96.7% with a mean distance from the emergence point (true anatomy) to the projected preoperative skin marking after PD mapping (assumed anatomy) of 2.45 ± 1.90 mm (0–6 mm) (Kehrer, Hsu, Chen, Sachanandani, & Tsao, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In line with this, we recently conducted an analysis of 44 ALT free flaps for distal upper extremity reconstruction with regard to the potential benefits and clinical relevance of preoperative color-coded Duplex ultrasonography ("Duplex") in comparison to handheld Doppler devices ("Doppler") (Thomas et al, 2020). Although we were able to show that Duplex significantly reduced both operative and harvest times of ALT free flaps in this select cohort of patients, the generalizability of our observations remains yet to be proven.…”
mentioning
confidence: 99%